Economic risks: classifcation, analysis and identifying their features under the conditions of the transformation period - Karpiyenia, Maryia V. (Journal of the Belarusian State University. Economics, 2022)
The stages of the historical development of the concept of economic risks, including modern ideas about this phenomenon, are reviewed. The classifcation of economic risks is given. The specifcity of economic risks in the transition period is analysed. Ways of measuring and evaluating economic risks, as well as transferring and insuring their consequences are being studied.